Senegal - Policies and Strategies for Accelerated Growth and Poverty Reduction : A Country Economic Memorandum - World Bank (Washington, DC, 2013)
This Country Economic Memorandum (CEM) finalized as the implementation period of the Poverty Reduction Strategy (PRSP) began, undertaken in a context of other significant investigations on PRSP themes. One of the main macroeconomic variables affecting growth and competitiveness of the Senegalese economy, is the nominal exchange rate, which, as a member of the West Africa Economic and Monetary Union (WAEMU), its currency, the CFA franc, has a fixed parity to the Euro, and its issuance is governed for all members, by a single central bank, where the nominal exchange rate is not a policy variable under Senegal's direct control. This is why the CEM does not take up issues concerning the nominal exchange rate, however, several measures of the real exchange rate are examined. CEM chapters on human capital include treatment of PRSP-related issues in health and education. The chapters present a portrait of constraints hindering progress toward PRSP targets, and the main interrelated points, first, between health and education, and second, between the public expenditure system and the delivery of health and education services to the poorest citizens. On social protection, the CEM analyzes important topics in tax incidence and pensions. Recommendations suggest Senegal should foster cooperation between unions, firms, and government, so as to shift all parties' focus away from dividing rents, toward the expansion of employment and production, creating a profitable business environment, with long term commitment to the marketplace, and, where the labor force is more likely to stimulate appropriate human capital formation. This calls for improvements in the overall efficiency of the education system, while systems of fiscal decentralization must b e adequate to the delivery of social services in all regions.